2020
DOI: 10.1093/icb/icaa100
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of 3D-printing in Biological Education: A Review of the Literature

Abstract: Abstract Science education is most effective when it provides authentic experiences that reflect professional practices and approaches that address issues relevant to students’ lives and communities. Such educational experiences are becoming increasingly interdisciplinary and can be enhanced using digital fabrication. Digital fabrication is the process of designing objects for the purpose of fabricating with machinery such as 3D-printers, laser cutters, and CNC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…Figure 7a shows student perceived positive benefits to their understanding and ability to visualize the instruments, and favored greater utilization of 3D printed instrument components. The favorable student outcomes and satisfaction are consistent with the positive results for 3D printed models used in anatomy, dentistry, and biochemistry [24].…”
Section: Student Responsesupporting
confidence: 73%
See 1 more Smart Citation
“…Figure 7a shows student perceived positive benefits to their understanding and ability to visualize the instruments, and favored greater utilization of 3D printed instrument components. The favorable student outcomes and satisfaction are consistent with the positive results for 3D printed models used in anatomy, dentistry, and biochemistry [24].…”
Section: Student Responsesupporting
confidence: 73%
“…While numerous laboratory examples have demonstrated the analytical use of 3D printing in the educational laboratory, little work has been demonstrated in the literature for analytical educational aids. A recent survey of over 450 papers describing 3D printing in biological education found only 13 studies that assessed benefits to students [24]. Of the four that measured changes in students' conceptual understanding, all saw improvements when students used printed models.…”
Section: Introductionmentioning
confidence: 99%
“…Formative assessments used in a makerspace classroom facilitate culturally responsive teaching where diverse perspectives are celebrated. For these reasons and more, the use of digital fabrication and 3D printing has become increasingly popular in biological education but our understanding of its value on student learning is still in its infancy ( Hansen et al 2020 ). In the examples here, it is demonstrated that fabrication projects motivate students to learn vertebrate anatomy, infusing a sense of fun into their formal higher education.…”
Section: Discussionmentioning
confidence: 99%
“…Now, with the tools available at a makerspace, anyone can change the world”. Researchers of “makification” in education ( Cohen et al 2016 ; Hansen et al 2020 ) “point out that the promise of the maker movement rests in its uniquely diverse communities with the encouragement of divergent mindsets that engage in multidisciplinary approaches to solve problems that are personally meaningful with potential to enrich meaning to those around them once they are shared”. Yet, studies note “trouble with the notion of makerspaces as an implicit panacea to equity and access issues in STEM” ( Barton et al 2017 ) unless we include “a broader range of identities, practices and environments” that represents “a bold step toward equity in education” ( Vossoughi et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%